Effects of obesity reduction on cardiovascular risk factors : comparison of individual and group treatment : substudy of the Croatian healthy weight loss programme - Jovanović, Željko, liječnik (Array, 2009)
Prevention of obesity may help reduce the morbidity and mortality from cardiovascular diseases. In Croatia, over half of adult population is overweight. Aldo the basic medical principles of healthy weight-loss programmes are well known, it is believed that mainly because of the leak of successful therapeutic approach obesity remains the most challenging changeable cardiovascular risk factor in nowadays clinical practice. Objective of this Croatian Healthy Weight Loss Programme substudy was to determine effects and differences between the intensive group and intensive individual weight-loss program on weight loss and cardiovascular risk factor.